Multiple Intelligences-based Islamic Religious and Ethics at SMP Negeri 3 Batang - Jimmy Malintang; Shodiq Abdullah; Nur Khoiri (Sekolah Tinggi Ilmu Tarbiyah Madani Yogyakarta, 2026)
The need for Islamic Religious Education (IRE) and ethics that can accommodate the diversity of students' intelligence. This study aims to analyze the background of the implementation of Multiple Intelligences-based IRE and ethics, teachers' implementation strategies, and their impact on academic outcomes, which include three aspects, namely cognitive, affective, and psychomotor aspects. This study uses a qualitative approach with a case study method at SMP Negeri 3 Batang. Data were collected through observation, in-depth interviews, and documentation, then analyzed using reduction, presentation, and conclusion drawing techniques. The results showed that PAI and Budi Pekerti learning based on Multiple Intelligences created an interactive, contextual, and humanistic learning atmosphere. Students were more motivated, actively involved in classroom activities, and experienced integrated strengthening of cognitive, affective, and psychomotor aspects. This study confirms the contribution of Howard Gardner's theory in designing learning that values student intelligence. Thus, this learning approach is relevant as a transformative strategy to produce a generation that is not only academically superior but also has character, is adaptive, and is able to face the challenges of 21st-century education.